Welding strength of NiTi wires - Mesquita,Tatyane Ribeiro (2018)
ABSTRACT Objective: To identify the appropriate power level for electric welding of three commercial brands of nickel-titanium (NiTi) wires. Methods: Ninety pairs of 0.018-in and 0.017 × 0.025-in NiTi wires were divided into three groups according to their manufacturers - GI (Orthometric, Marília, Brazil), GII (3M OralCare, St. Paul, CA) and GIII (GAC,York, PA) - and welded by electrical resistance. Each group was divided into subgroups of 5 pairs of wires, in which welding was done with different power levels. In GI and GII, power levels of 2.5, 3, 3.5, 4, 4.5 and 5 were used, while in GIII 2.5, 3, 3.5 and 4 were used (each unit of power of the welding machine representing 500W). The pairs of welded wires underwent a tensile strength test on an universal testing machine until rupture and the maximum forces were recorded. Analysis of variance (ANOVA) and post-hoc tests were conducted to determine which subgroup within each brand group had the greatest resistance to rupture. Results: The 2.5 power exhibited the lowest resistance to rupture in all groups (43.75N for GI, 28.41N for GII and 47.57N for GIII) while the 4.0 power provided the highest resistance in GI and GII (97.90N and 99.61N, respectively), while in GIII (79.28N) the highest resistance was achieved with a 3.5 power welding. Conclusions: The most appropriate power for welding varied for each brand, being 4.0 for Orthometric and 3M, and 3.5 for GAC NiTi wires.